Faktor-Faktor yang Mempengaruhi Perilaku Dosen STAI Auliaurrasyidin Tembilahan dalam Memilih Produk Bank Syariah - Siti Zariah (AL-Muqayyad, 2021)
This research was motivated by The sharia economy is now entering the world of education, in addition to banks and other non-bank financial institutions that are busy adding the "sharia" label to their institutions. TThe purpose of this research is to find out and analyze The factors that influence the behavior of STAI Lecturer Auliaurrasyidin through cultural, social, personal, psychological and knowledge factors as moderating variables in choosing Islamic bank products in Tembilahan. This research was conducted at STAI Auliaurrasyidin Tembilahan with the number of respondents as many as 32 permanent lecturers. The method used in this quantitative research is the survey method. This research is a mixed research, which combines quantitative and qualitative research. The results of the study based on the correlation coefficient analysis test showed that the level of influence of the variables of consumer behavior factors, namely cultural factors, social factors, personal factors and psychological factors simultaneously on the decision of STAI Lecturer Auliaurrasyidin Tembilahan in choosing Islamic bank products was worth 0.776 and the level of the relationship was in the category " strong" or "high" while the knowledge moderation variable is worth 0.411 and the level of the relationship is in the "medium" or "fair" category